Effects of Live Combined Bacillus subtilis and Enterococcus faecium on Gut Microbiota Composition in C57BL/6 Mice and in Humans - Pi, Xionge; Teng, Weilin; Fei, Dibo; Zhao, Gang; Liu, Wei (Frontiers in Cellular and Infection Microbiology, 2022)
Probiotics, prebiotics, and synbiotics can alleviate metabolic syndrome by altering the composition of the gut microbiota. Live combined Enterococcus faecium and Bacillus subtilis has been indicated to promote growth and reduce inflammation in animal models. However, the modulatory effects of live combined B. subtilis R-179 and E. faecium R-026 (LCBE) on human microbiota remain unclear. The current study examined the growth of these two strains in the presence of various oligosaccharides and assessed the effects of this probiotic mixture on human and murine gut microbiota in vitro and in vivo. Oligosaccharides improved the growth of E. faecium R-026 and B. subtilis R-179 as well as increased their production of short-chain fatty acids. E. faecium R-026 or B. subtilis R-179 co-incubated with Bifidobacterium and Clostridium significantly increased the number of the anaerobic bacteria Bifidobacterium longum and Clostridium butyricum by in vitro fermentation. Moreover, LCBE significantly reduced plasma cholesterol levels in mouse models of hyperlipidemia. LCBE combined with galacto-oligosaccharides led to a significant decrease in the Firmicutes/Bacteroidetes ratio and a significant increase in the relative abundance of Akkermansia and Bifidobacteria after treating mice with LCBE (0.23 g/day) for eight weeks. Furthermore, in vitro fermentation also showed that both the single strains and the two-strain mixture modulated human gut microbiota, resulting in increased Lactobacillus and Bifidobacteria, and decreased Escherichia-Shigella. Overall, these results suggest that LCBE can improve host health by reducing the level of cholesterol in mouse models by modifying the composition of the gut microbiota.